"Objectivity" as a bureaucratic virtue: Cultivating unemotionality in an Israeli medical committee. (27th May 2021) - ASSOR, YAEL
ABSTRACT: Across bureaucratic contexts, "objectivity" is a dominant conception of appropriate conduct. But what does it mean for bureaucrats to work "objectively"? For staffers of the Israeli government's Committee for Health Care Services, objectivity is understood as a key bureaucratic virtue, one that promotes the ethical goal of fair resource allocation. To them, objective decision‐making is based on adopting an "unemotional" attitude. Aware of the life‐and‐death implications of committee decisions, they attempt to work "unemotionally" by engaging what I term a moral sensibility for unemotionality, a tendency to avoid exposure to patients' subjective experience. Cultivating this sensibility has concrete effects on the committee's decisions and on patients' place in medical decision‐making. Examining "objectivity" as a morally desired disposition, rather than as a static construct, yields its reconceptualization as an enduring intersubjective achievement. This approach offers another way to examine the workings of power and politics in state bureaucracies. [ objectivity, bureaucracy, virtue ethics, morality, emotion, social welfare, health care, Israel ] خُلاصة،: تعتبر "الموضوعية" مبدأً مركزياً للسلوك السليم في العديد من المؤسسات البيروقراطية. ومع ذلك، كيف يُنظر إلى العمل "الموضوعي" بين البيروقراطيات من الناحية العملية؟ بالنسبة للنساء العاملات في وزارة الصحة اللواتي يعدن المعلومات التي تستند إليها مناقشات اللجنة العامة لتوسيع سلة الأدوية، يُنظر إلى العمل الموضوعي على أنه إجراء جيد يجب رعايته من أجل تعزيز التوزيع العادل للموارد. بالنسبة لهن، وإن العمل الموضوعي يعني اتباع نهج "غير عاطفي". وإدراكًا منهم للآثار الوخيمة لقرارات لجنة سلة الادوية على حياة (ووفيات) المرضى، يحاول أعضاء الطاقم تعزيز هذا النهج من خلال تجنب التعرض للتجربة الشخصية للمرضى. لدى هذا النمط من العمل آثار حقيقية على قرارات لجنة سلة الأدوية واستبعاد المر   ضىى من عمليات تخطيط السياسة الصحية في إسرائيل. يؤدي الفحص المقترح هنا ل "الموضوعية" كوقف أخلاقي مرغوب فيه وليس كوصف لحالة ثابتة إلى إعادة تصور "الموضوعية" كعملية مستمرة بين الذات. يثير هذا التصور طريقة أخرى لفحص السياسة وعلاقات القوة بين البيروقراطيات الحكومية. [الموضوعية، البيروقراطية، الفضيلة، الأخلاق، إسرائيل، الرعاية الصحية، رفاهية إجتماعية, العاطفة]. תקציר: "אובייקטיביות" נחשבת לעקרון מרכזי של התנהלות נאותה במוסדות ביורוקרטיים רבים. אולם, כיצד עבודה "אובייקטיבית" נתפסת בקרב הפקידות הביורוקרטית הלכה למעשה? עבור נשות צוות משרד הבריאות המכינות את המידע עליו מתבססים דיוני הועדה הציבורית להרחבת סל התרופות, עבודה אובייקטיבית נתפסת כמידה טובה שיש לטפח לשם קידום חלוקת משאבים הוגנת. לדידן, משמעותה של עבודה אובייקטיבית היא נקיטת גישה "לא‐רגשית". מודעות להשלכות הכבדות של החלטות ועדת סל התרופות על חייהם (ומותם) של חולים, חברות הצוות מנסות לטפח גישה זו על ידי הימנעות מחשיפה לחוויה הסובייקטיבית של החולים. לתבנית פעולה זו השלכות ממשיות על החלטות ועדת סל התרופות ועל הדרתם של חולים מתהליכי תכנון מדיניות בריאות בישראל. הבחינה המוצעת כאן של "אובייקטיביות" כעמדה מוסרית נחשקת ולא כתאור מצב סטטי, מביאה להמשגה מחודשת של "אובייקטיביות" כתהליך אינטר‐סובייקטיבי מתמשך. המשגה זו מעלה דרך נוספת לבחינת הפוליטיקה ויחסי הכוח שבביורוקרטיות ממשלתיות. [אובייקטיביות, ביורוקרטיה, אתיקה של המידה הטובה, מוסר, ישראל, מערכת הבריאות, רווחה חברתית, רגש]